2010
DOI: 10.1016/j.clinbiochem.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The use of a cytokine panel to define the long-term risk stratification of heart failure/death in patients presenting with chest pain to the emergency department

Abstract: Objective-To determine if a cytokine panel could be informative regarding subsequent heart failure (HF)/death.Design and methods-In 216 subjects presenting with chest pain to an emergency department in 1996, EDTA plasma (−70 °C) was thawed for IL-6, MCP-1, IL-10, VEGF, EGF measurement.Results-Subjects with any three cytokines elevated were at higher risk for HF/death compared to those with ≤two cytokines elevated.Discussion-A cytokine panel might be useful for risk stratification for HF/death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…45,46 Furthermore, these specific markers and assays have been measured in plasma stored for a decade in another population at risk for cardiac injury, thus suggesting clinical utility and mitigating stability issues. 47 As few of the TRIBE participants were off-pump (9%), we could not evaluate whether the use of cardiopulmonary bypass modified the association of angiogenic markers and our specified outcomes. Prior literature has shown an increase in VEGF levels for on-pump versus offpump cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Furthermore, these specific markers and assays have been measured in plasma stored for a decade in another population at risk for cardiac injury, thus suggesting clinical utility and mitigating stability issues. 47 As few of the TRIBE participants were off-pump (9%), we could not evaluate whether the use of cardiopulmonary bypass modified the association of angiogenic markers and our specified outcomes. Prior literature has shown an increase in VEGF levels for on-pump versus offpump cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with human subjects have shown differences regarding results. Kavsak et al (17), in a study of 216 patients, reported that high IL-6 levels were a significant predictor of HF in the first 6 months, 2 years, and 8 years post-event (6 months: HR 3.79, 95%CI: 1.28–11.19, P=0.016; 2 years: HR 3.27, 95%CI: 1.48–7.20, P=0.003; and 8 years: HR 2.57, 95%CI: 1.58–4.19, P=0.001). Hartford et al (18), in an analysis of 134 patients with AMI after a 30-month follow-up, did not find any significant differences in IL-6 levels between patients who were hospitalized for HF and those who were not (18.9 vs 17.5 pg/mL, P=0.39).…”
Section: Discussionmentioning
confidence: 99%
“…These parameters are: type of anticoagulant, assay method, center performing the measurement, type of centrifuge, sex of the participant. These parameters are extremely important to consider when systemic VEGF-A is measured for example as part of a safety evaluation after anti-VEGF therapy or in other fields, where systemic VEGF-A levels are of importance for example in evaluating clinical outcome [ 18 20 ] or in providing risk estimates [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%